2013
DOI: 10.1371/journal.ppat.1003335
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Monokaryotic Hyphae by Cryptococcus neoformans Can Be Induced by High Temperature Arrest of the Cell Cycle and Is Independent of Same-Sex Mating

Abstract: Cryptococcus neoformans is a heterothallic fungal pathogen of humans and animals. Although the fungus grows primarily as a yeast, hyphae are produced during the sexual phase and during a process called monokaryotic fruiting, which is also believed to involve sexual reproduction, but between cells of the same mating type. Here we report a novel monokaryotic fruiting mechanism that is dependent on the cell cycle and occurs in haploid cells in the absence of sexual reproduction. Cells grown at 37°C were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Thus, the wild type, which is proficient in unisexual reproduction, gains an advantage not only by habitat exploration through hyphae but also by dominating the surrounding environment through the production of recombinant spores that can readily be further disseminated aerially. This is notable because C. neoformans can undergo sporadic hyphal development without the production of spores through an unknown pathway that is independent of unisexual reproduction (13). Furthermore, spores disseminated following unisexual reproduction can serve as infectious propagules (14).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the wild type, which is proficient in unisexual reproduction, gains an advantage not only by habitat exploration through hyphae but also by dominating the surrounding environment through the production of recombinant spores that can readily be further disseminated aerially. This is notable because C. neoformans can undergo sporadic hyphal development without the production of spores through an unknown pathway that is independent of unisexual reproduction (13). Furthermore, spores disseminated following unisexual reproduction can serve as infectious propagules (14).…”
Section: Resultsmentioning
confidence: 99%
“…More intriguing, the developmental cascades for both modes of reproduction have been found to be controlled by the same genetic circuits, demonstrating that the spores produced in unisexual reproduction are also the result of meiosis (Lin et al 2005;Feretzaki and Heitman 2013). Furthermore, a recent report indicates that monokaryotic hyphal production unrelated to unisexual reproduction can be induced by high-temperature arrest of yeast cell cycle in the G 2 stage (Fu et al 2013). Whether the genetic circuits that control monokaryotic hyphal formation induced by high-temperature cell-cycle arrest at G 2 overlap with those of sexual reproduction is a compelling question that remains to be determined.…”
Section: Mycology Life Cyclementioning
confidence: 99%
“…The yeast-hyphal transition was once considered a hallmark for Cryptococcus mating; however, evidence has shown that there is also a sex-independent form of thermally activated hyphal growth (Fu et al, 2013). Bilateral mating between two znf2 Δ α cells failed to initiate the morphological transition despite the fact that diploid cells can be easily detected (Wang and Lin, 2011).…”
Section: Foraging For Mating Partners and Nutrientsmentioning
confidence: 99%